2012
DOI: 10.4040/jkan.2012.42.6.879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Proficiency and Parent-child Cohesion on Self-esteem and Acculturation among Children from Multicultural Families

Abstract: Purpose: There is evidence that parent-child cohesion is a potentially influential factor in children's self-esteem and acculturation. However, no research to date has examined cohesion with parents as a potential pathway between Korean proficiency and self-esteem or acculturation among children from multicultural families. This study was done to address these limitations by examining whether and to what extent cohesion with parents mediated the effect of Korean proficiency on self-esteem and acculturation amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This occurs because the mothers of these children are poor in the Korean language (Kim et al 2012). Most responses in the study on stress and dissatisfaction among foreign laborers in Korea indicated communication problems (You 2005).…”
Section: Problem: Hidden Unstable Futurementioning
confidence: 97%
“…This occurs because the mothers of these children are poor in the Korean language (Kim et al 2012). Most responses in the study on stress and dissatisfaction among foreign laborers in Korea indicated communication problems (You 2005).…”
Section: Problem: Hidden Unstable Futurementioning
confidence: 97%
“…Family relationship quality, which is assessed as family cohesion, support, communication, and subjective satisfaction, also plays an important role in the overall psychological adaptation of MY. It decreases mental health risks such as depression, anxiety, and suicidal ideation [28,31,[33][34][35][36] and improves self-esteem [37]. In contrast, the risk for depression was high among MY who spent less time conversing with their fathers and those whose parents showed a low degree of interest in them [29].…”
Section: Familial Factorsmentioning
confidence: 99%
“…As of 2011, the number of children from multicultural families had reached 155,000, which accounts for approximately 11.9% of the entire foreign population of Korea. This is a substantial increase from 2006, in which the number of children from multicultural families was 25,000 2 ) . However, it has been reported that children from multicultural families may be faced with serious difficulties in acculturation because of differences in their cultural and historical background, language, culture, and education methods, low socioeconomic status, and communication problems 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid-1990s, a large number of women from developing countries have been immigrating to South Korea through international marriages. As a result, the number of children born to multicultural families is burgeoning 1 , 2 ) . As of 2011, the number of children from multicultural families had reached 155,000, which accounts for approximately 11.9% of the entire foreign population of Korea.…”
Section: Introductionmentioning
confidence: 99%